Anthropometrics, Athletic Abilities and Perceptual-Cognitive Skills Associated With Baseball Pitching Velocity in Young Athletes Aged Between 10 and 22 Years Old - Tremblay, Mathieu; Tétreau, Charles; Corbin-Berrigan, Laurie-Ann; Descarreaux, Martin (Frontiers in Sports and Active Living, 2022)
The purpose was to identify across ages, in younger male and female, and to compare, in younger male, the anthropometrics and athletic abilities associated with baseball pitcher’s performance, aged 10 to 22 years old. A cross-sectional design was used to conduct this study. Male and female athletes completed a sociodemographic questionnaire followed by anthropometric, athletic ability, and throwing performance assessments. Athletes were categorized by their age categories (11U, 13U, 15U, 18U, 21U). To evaluate the athletes’ anthropometrics, height and weight, BMI, arm segmental length and girth were measured. Athletic abilities were assessed using athletes’ grip strength, upper body power, vertical jump height, sprint, change of direction, dynamic balance, and perceptual-cognitive skills performance. Pitching performance assessment was completed using the athletes’ average pitching velocity. Kendall Tau’s correlation coefficient was used to assess relationships between variables and pitching performances in male athletes (p ˂ 0.05). A 1-way ANOVA was performed to identify differences between age categories for all variables in male athletes (p ˂ 0.05). In male athletes, without age categories discrimination, all anthropometric and athletic ability variables were associated with pitching performance, and differences exist between age categories. Descriptive data of female athletes results regarding anthropometrics, athletic abilities and pitching performance are also presented.